Pengaruh Kemampuan Berpikir Kreatif Terhadap Kemampuan Koneksi Matematika Siswa SMK Tarbiyatul Qurro’ Tahun Pelajaran 2022/2023 - Putri, Fitri Liani; Nissa, Itha Chairun; Yuliyanti, Sri (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
Abstract: The purpose of this study was to determine the effect of creative thinking skills on students' mathematical connection abilities. The type of research used is ex post facto with a quantitative approach. The sampling technique used in this study was a purposive sampling technique, while the samples selected in this study were 34 students from class X SMK Tarbiyatul Qurro' Selagalas, Mataram City. The instrument used in this study was in the form of description questions which amounted to one item covering the ability to think creatively and one item covering the ability to connect mathematics. The data analysis technique used is the T test and simple linear regression. Before carrying out linear regression analysis, prerequisite tests must be carried out, namely homogeneity, normality and linearity tests. The homogeneity test uses Fisher's test. The results of homogeneity calculations using Fisher's test with manual calculations found that F_count = 1.116 and F_table = 1.787. Because F_count< F_table, the two groups are said to be homogeneous. The results of the simple linear regression equation are Y ̂ = a + bX = 36.892+ 0.725X. As for the results of the calculation of the influence test with the T test, obtained T_count = 5.241 and T_table = 2.036 because T_count < T_table with a significant level of 5%, it is concluded that there is a real (significant) influence ) creative thinking skills on students' mathematical connection abilities.